Lagenorhynchus albirostris J. E. Gray 1846 - Galatius, Anders; Kinze, Carl Christian (Zenodo, 2016)
Lagenorhynchus albirostris J. E. Gray, 1846a White-beaked Dolphin Delphinus Tursio Brightwell, 1846:21, plate 1. Not Delphinus tursio Fabricius, 1780. Lagenorhynchus albirostris : J. E. Gray. 1846a:84. No type locality specified, but stated as “North Sea, coast of Norfolk ” by Gray (1846b:35); restricted by Gray (1850) to Great Yarmouth. First use of current name combination. Delphinus albirostris : J. E. Gray, 1846b:35, plate 10. Incorrect reference to Lagenorhynchus albirostris (Gray, 1846a) Delphinus pseudotursio Reichenbach, 1846:plate 24, figure 76. New name based on Brightwell’s (1846) description (see “Nomenclatural Notes”). Delphinus Ibsenii Eschricht, 1846:297. Type locality: “Agger Tange,” West coast of Jutland, Denmark. Delphinus (Lagenorhynchus) albirostris: van Beneden, 1860:28. Name combination. CONTEXT AND CONTENT. Order Cetacea, suborder Odontoceti, family Delphinidae. Subfamily assignment remains unsettled. Traditionally, the genus Lagenorhynchus comprised 6 shortsnouted delphinid species. Molecular research, however, has found this grouping to be polyphyletic, that is, comprising at least 2 unrelated lineages: (1) the Pacific and Southern ocean members ( L. obliquidens , and L. obscurus , L. australis , and L. cruciger , respectively), assigned to the subfamily Lissodelphininae; and (2) the 2 North Atlantic members of the genus ( L. albirostris and L./ Leucopleurus acutus — Cipriano 1997; LeDuc et al. 1999; Harlin-Cognato and Honeycutt 2006; McGowen et al. 2009; McGowen 2011; Banguera-Hinestroza et al. 2014). Molecular studies addressing the relationship between the latter 2 species have provided conflicting results (LeDuc et al. 1999; Harlin-Cognato and Honeycutt 2006; Banguera-Hinestroza et al. 2014). All studies agree that the taxa have basal positions in the Delphinidae phylogeny, but they either represent separate lineages (subfamilies) within the dolphin family (Delphinidae) or they are indeed sister species and form their own subfamily Lagenorhynchinae (Banguera- Hinestroza et al. 2014). In the latter case, the time of their divergence has been estimated as far back as 11.49 million years ago, which may merit assignment to separate genera (Banguera-Hinestroza et al. 2014). NOMENCLATURAL NOTES. Brightwell’s (1846) description of a dolphin from Great Yarmouth that he assigned to Delphinus Tursio of Fabricius (1780) was promptly corrected by Gray (1846a) in what is considered the formal description of the white-beaked dolphin. In this and his later paper (1846b), Gray applies Lagenorhynchus as the generic name, although in his 2nd account (Gray 1846b), he incorrectly credited himself for applying the name Delphinus albirostris in the 1st account (Gray 1846a). Later, the binomen Delphinus albirostris was used by Gray and many others. The work of Reichenbach (1846) does not include a description of the new species in the text but contains on plate XXIV, as number 76, a mirrored version of Brightwell’s (1846) original figure with a caption reading: Delphinus pseudotursio Rchb. D. Tursio Th. Brightwell. An. Mag Hist. 1846 . Hereby Reichenbach, independently from Gray (1846a, 1846b) recognized Brightwell’s dolphin as a new species. The new species name chosen by Reichenbach, clearly is based on Brightwell’s specimen and therefore available, but since no exact date of publication could be established it falls into junior synonymy. Wagner (1846) provided a short Latin description of the species and in the accompanying plate volume (Wagner 1847), a mirrored version of the original Brightwell (1846) drawing. He considered Lagenorhynchus a subgeneric name introduced by Gray and consequently named it D [ elphinus ]. albirostris. Generic and subgeneric names were often used interchangeably. van Beneden (1860) for the 1st time gave the scientific name in full: Delphinus ( Lagenorhynchus ) albirostris , but later, he used both Delphinus albirostris and Lagenorhynchus albirostris . Eschricht (1846) gave a short description of the skeleton of a new dolphin species he intended to describe under the name Delphinus Ibsenii , but he never published an extended description. Gray (1850) and Claudius (1853) put Delphinus Ibsenii into the synonymy of Lagenorhynchus albirostris . Kinze (2009) established that Gray’s specific name ( albirostris ) antedates Eschricht’s and therefore is to be considered the senior synonym. Delphinus tursio was still in use for specimens of whitebeaked dolphins until at least 1861 (Sundevall 1861). Several European museums hold specimens of the white-beaked dolphin originating from waters around Greenland and collected before the formal description in 1846, these were originally assigned to Delphinus delphis. The name, Lagenorhynchus , is composed of the Latin word lagena , meaning bottle or flask, and the Greek word rhynchus , meaning snout. The specific name, albirostris (Latin: whitebeaked), refers to the common, but not universal, white beak. Additional common names for L. albirostris include the following: hvidnaese (Danish); witsnuitdolfijn (Dutch); kjarthvitur springari (Faroese); dauphin avec bec blanc (French); Weissschnauzendelfin (German); ardluarsuk (Greenlandic); Blettahnýðir or Hnýðingur (Icelandic); deilf na ngoba bána (Irish); kvitnos (Norwegian); delfin bialosy (Polish); belomordyi del’fin (Russian); delfin de hocicio blanco (Spanish); vitnosdelfin (Swedish). It is commonly referred to as “springer” or “jumper,” especially in parts of Canada, the Faroes, and Norway. These latter names are also used to refer to the Atlantic whitesided dolphin. DIAGNOSIS Lagenorhynchus albirostris is most likely to be confused with the Atlantic white-sided dolphin, L . acutus , from which it differs by the white or gray beak, a light gray-to-white saddle behind the dorsal fin, and the lack of a yellow field on the posterior flank. Skulls of L . albirostris can be distinguished from those of other North Atlantic delphinids by a toothrow with more than 20 teeth and by the shorter (<240 mm) and wider (> 125 mm) rostrum. Skeletons of L . albirostris differ from those of other cetaceans by the high vertebral count, 88–93. Only right whale dolphins ( Lissodelphis —up to 90 vertebrae) and Dall’s porpoise ( Phocoenoides dalli —up to 98 vertebrae), both absent in the North Atlantic, reach this range. GENERAL CHARACTERS Lagenorhynchus albirostris is robust compared to most other delphinids, with a comparatively short, thick beak protruding 5–8 cm from the offset of the melon. The tall, falcate dorsal fin is located around mid-length. Coloration is complex and changes during ontogeny, this has been described and broken into components by Bertulli et al. (2016). As the vernacular name implies, white-beaked dolphins have a white or whitish beak, which in many, particularly adult individuals, is darkened to an ashy gray (Bertulli et al. 2016). The color of the beak often continues backward a few cm posterior to the base of the melon. The dorsum, flanks, and the remainder of the melon are dark gray, whereas the dorsal fin, flippers, and fluke are generally dark gray except for a white or light gray saddle behind the dorsal fin and the occurrence of light patches on the anterior leading edges of fin and flippers in adults. A light patch surrounds the eye, with a darker section immediately around the eye. The dark gray areas of the dorsum and flanks are overlaid by a lighter gray blaze starting near the anal region and extending dorso-anteriorly along the peduncle and flank to the level of the flippers. Another light gray area on the anterior (thoracic) flank lies between the flipper and the flank patch. The belly is entirely light gray-to-white with a narrow white medial band from the flippers to the genital slit (Figs. 1 and 2). This general pattern varies among ontogenetic stages, individuals, and possibly geographic areas (Harmer 1927; Mercer 1973; Camphuysen 1991; Ree 1994; Bertulli et al. 2016). The longest known specimen is a 310 cm male from the British Isles (Fraser 1974), but few specimens reach 300 cm in total length (Guldberg and Nansen 1894; Harmer 1927; Galatius et al. 2013a). Adult males are larger than females (Dong et al. 1996) due to an extended period of growth (Galatius et al. 2013a). In a sample from the North Sea, adult females were 242–265 cm with a mean length of 251 cm and males were 252–290 cm with a mean of 273 cm (Galatius et al. 2013a). Ranges of selected body measurements (cm; by C. C. Kinze) from adult females and males, respectively, stranded in the eastern North Sea were: dorsal fin height, 22–38 ( n = 19) and 26–40 ( n = 15); anterior flipper length, 32–48 ( n = 21) and 36–52 ( n = 19); fluke span, 42–70 ( n = 18) and 52–83 ( n = 17); and snout to center of genital aperture, 90–120 ( n = 15) and 75–90 ( n = 16). The observation of a pregnant female only 174 cm long suggests that L . albirostris may reach adulthood at smaller sizes in the western North Atlantic (Dong et al. 1996). Few weights have been reported, the largest known male weighed 354 kg (van Utrecht 1981) and the largest female 306 kg (Reeves et al. 1999). Means and ranges (mm; by A. Galatius) of selected cranial measurements of adult females and males, respectively, from the eastern North Sea were: condylobasal length, 444 (415–452; n = 16), 451 (435–464; n = 12); rostral length, 219 (206–227; n = 17), 220 (212–226; n = 12); rostral width at base, 139 (130–145; n = 16), 143 (132–153; n = 12); width at antorbital processes, 228 (216–241; n = 16), 234 (222–246; n = 12); zygomatic width, 243 (233–257; n = 16), 253 (240–266; n = 12); right mandible length, 369 (350–385; n = 17), 376 (354–391; n = 15); length of right upper toothrow, 192 (182–202; n = 16), 194 (188–202; n = 12). The skull has large, deep temporal fossae and robust antorbital, postorbital, and zygomatic processes (Fig. 3). DISTRIBUTION Lagenorhynchus albirostris is endemic to the cooler temperate and subarctic North Atlantic (Reeves et al. 1999; Fig. 4). Four principal centers with higher density have been identified (Kinze 2009): (1) The Labrador Shelf and southwestern Greenland; (2) around Iceland; (3) around the northern part of the British Isles and the North Sea; (4) the shelf along the Norwegian coast, including the Barents Sea. In (1), the species has been recorded from western Greenland in the North (71°) to Cape Cod, Massachusetts (Alling and Whitehead 1987; Kingsley and Reeves 1998; Waring et al. 2008; Lawson and Gosselin 2009; Hansen and Heide-Jørgensen 2013). Apart from 2 recent sightings near the southeastern coast of Baffin Island, the species is unknown in this area (Reinhart et al. 2014). In (2), L . albirostris is the most common dolphin (Vikingsson and Ólafsdóttir 2004; Pike et al. 2009). This area may also extend to southeastern Greenland, where it is also the most common dolphin (Jonsgård and Christensen 1968). In (3), the highest sighting rates are from the Outer Hebrides and in the western North Sea, but its distribution also extends into the central North Sea to the Danish coast, around Ireland and even some sightings in the English Channel (Northridge et al. 1995, 1997; Hammond et al. 2002; Reid et al. 2003; Hammond et al. 2013). In (4), distribution of L . albirostris extends throughout the western Barents Sea except for the northernmost parts (Øien 1996; Fall and Skern-Mauritzen 2014). FOSSIL RECORD There is no fossil record of the taxon. Subfossil remains from the greater North Sea and Baltic Sea area document its presence in European waters since the last glacial period (Aaris-Sørensen et al. 2010). Degerbøl (1936) reported subfossils from the medieval Norse West Settlement in Greenland. FORM AND FUNCTION The dental formula of Lagenorhynchus albirostris is 25–28 homodont teeth in each jaw, but the 3 anteriormost teeth often do not protrude from the gums (van Bree and Nijssen 1964). Vertebral formula is 7 C, 15–16 T, 23–24 L, 43–45 Ca, total 88–92 vertebrae (Lütken 1888; True 1889) or 7 C, 14 T, 27 L, 45 Ca, total 93 (Tomilin 1967). This is the highest count of vertebrae in a delphinid. The vertebrae have short, wide centra and long spinal and transverse processes. Such vertebral morphology is an adaptation to fast, dynamic swimming at the expense of flexibility (Buchholtz 2001). We have observed that the first 2 cervical vertebrae are always fused, but often all 7 are fused. The phalangeal formula is I2, II6, III4, IV1, V0 (Tomilin 1967). In most specimens, the right humerus is longer and more robust than the left, indicating lateralized behavior, something that has been recorded in several cetacean species (Galatius 2006). The 2–4 vibrissae on each upper lip in fetuses and neonates (Turner 1889; Japha 1912) disappear during development as in other Odontoceti and adults have none. The integumentary blubber is 18–31 mm thick, except for the fins and flukes in which a countercurrent heat exchange system operates to conserve heat (Scholander and Schevill 1955). The organ systems of L . albirostris exhibit a typical delphinid organization (muscular system—Murie (1873); nervous system: spinal cord—Cunningham (1877), brain—Weber (1887); sensory system—Fraser (1952); lungs—Cleland (1884) and Weber (1887); digestive system: stomach—Clark (1876), Cleland (1884), Weber (1887), and Turner (1889), small and large intestine—van Beneden (1860) and Cleland (1884); circulatory system: blood vessels—Slijper (1936), heart—Smet et al. (1985) and van Nie (1985, 1986); female reproductive system—van Beneden (1860) and Meek (1918); functional anatomy of mammary slits—Gylling (1912)). In animals from the North Sea ( n = 10), the lungs weighed 1,100 –2,000 g (left) and 1,300 –2,200 g (right). Heart masses were 800–1,900 g, liver masses 1,800 –3,400 g, and kidneys weighed 300–600 g each. Adrenals are tiny: 2–8 g (Reeves et al. 1999; and measured by C. C. Kinze). ONTOGENY AND REPRODUCTION Ontogeny. —Some highly specialized information is known only from single fetal specimens of Lagenorhynchus albirostris (larynx—Thompson 1890; retina—ten Doesschate 1918). Length at birth is estimated at 110–120 cm (Tomilin 1967; Collet and Duguy 1981), but the age and length at weaning are not known. Growth has only been thoroughly investigated in a North Sea sample of 64 females and 52 males (Galatius et al. 2013a). During the first 3 years, young of both sexes grew to about 210 cm, after which growth rate slowed somewhat. Females reached 95% of asymptotic length by about 5.2 years but males continued growing 5 more years, resulting in sexual size dimorphism. Females become sexually mature at 6–10 years and 230–240 cm in length. Males become sexually mature about 2 years later than females and are typically 230–260 cm in length. Adult size of the cranium is achieved at about 6 years of age in the North Sea population ( n = 81), whereas sutures of the skull are not fully developed until about 9 years of age (Galatius 2010). Reproduction. —Paired testes mass in 16 adults from the North Sea showed annual fluctuations from about 700 g during the winter to near 2,100 g during the boreal summer, suggesting that mating occurs in the latter period (Galatius et al. 2013a). Around the United Kingdom, strandings of calves below 130 cm in length are reported almost exclusively between June and September, supporting that parturition occurs during this time (Fraser 1974; Canning et al. 2008). Gestation is believed to last about 11 months (Reeves et al. 1999), litter size is 1 as in other Cetacea. Only 3 of 22 sexually mature females were lactating and only 1 was pregnant in the North Sea sample of Galatius et al. (2013a). This observation indicates either a significant resting period between parturitions or segregation of reproductively active females from others. ECOLOGY Population characteristics. —Skull morphometric evidence suggesting segregation between the eastern and western North Atlantic populations of Lagenorhynchus albirostris (Mikkelsen and Lund 1994) was confirmed by a molecular study (Banguera-Hinestroza et al. 2010), which also found segregation between dolphins from the United Kingdom and North Sea and those from northern Norway. The latter study did not include samples from Iceland or Greenland; thus, population structure throughout the range of the species remains unresolved. Using> 50,000 single nucleotide polymorphisms, Fernandez et al. (2016) detected 2 genetic clusters among 70 L. albirostris sampled throughout the eastern North Atlantic. Aerial surveys conducted from 1978 to 1982 for the shelf waters from Cape Hatteras to Nova Scotia yielded a population abundance estimate of 573 ( CV : 0.69— Cetacean and Turtle Assessment Program 1982). Aerial surveys in the 1980s off eastern Newfoundland and the Labrador coast yielded an estimate of 5,500 L . albirostris (no CV —Alling and Whitehead 1987). An abundance of 3,486 individuals (95% CI : 2,001 –4,971) was estimated from a shipboard survey of a small segment of the Labrador shelf in 1982 (Alling and Whitehead 1987). Aerial surveys in 1995 and 1996 in the Gulf of St. Lawrence yielded estimates of 2,640 ( SE : 2,080) and 2,380 ( SE : 2,540), respectively (Kingsley and Reeves 1998), and a 2007 aerial survey of the Canadian shelf from north Labrador to the United States border gave a preliminary estimate of 1842 ( CV : 0.22—Lawson and Gosselin 2009). A coast-to- 90 km aerial survey of the shelf of West Greenland up to 71°N yielded an estimate of 11,984 ( CV : 0.19) L . albirostris in 2007 (Hansen and Heide-Jørgensen 2013). Aerial surveys in Icelandic waters in 2001 yielded a point estimate of 31,653 (95% CI : 17,679 –56,672 — Pike et al. 2009). This estimate also included other dolphin species, although the overwhelming majority of the sightings were L . albirostris . In the greater North Sea, shipboard surveys in 1994 yielded an estimate of 7,856 individuals ( CV : 0.30— Hammond et al. 2002). A 2005 estimate for this area was 16,536 ( CV : 0.30— Hammond et al. 2013). The latter survey covered an area to the west that was not covered in 1994 and showed high density in 2005. The design of this survey was criticized for being inappropriate for the patchy distribution of L . albirostris (MacLeod 2014). In their response, Hammond et al. (2014) maintained that the design was appropriate for large-scale abundance estimates, but not f : Published as part of Galatius, Anders & Kinze, Carl Christian, 2016, Lagenorhynchus albirostris (Cetacea: Delphinidae), pp. 35-47 in Mammalian Species 48 (933) on pages 35-43, DOI: 10.1093/mspecies/sew003, http://zenodo.org/record/4573390 : {"references": ["GRAY, J. E. 1846 a. On the British Cetacea. Annals and Magazine of Natural History 17: 82 - 85.", "BRIGHTWELL, T. 1846. Observations on a specimen of the bottlenosed dolphin, Delphinus Tursio, Fabr., taken at Great Yarmouth, October 1845. The Annals and Magazine of Natural History 17: 21 - 22.", "FABRICIUS, O. 1780. Fauna Groenlandica: systematice sistens animalia Groenlandiae occidentalis hactenus indagata, quad nomen specificum, triviale, vernaculumque: synonyma auctorum plurium, descriptionem, locum, victum, generationem, mores Othonis Fabricii. Ioannis Gottlob Rothe, Copenhagen, Denmark.", "GRAY, J. E. 1846 b. On the cetaceous animals. Pp. 13 - 53 in Zoology of the voyage of HMS Erebus and Terror under the command of Sir James Clark Ross, R. N., F. R. S., during the years 1839 to 1843, vol. I mammals, birds (J. Richardson and J. E. Gray, eds.). E. W. Janson, London, United Kingdom.", "GRAY, J. E. 1850. Catalogue of the specimens in the collection of the British Museum, part one Cetacea. Trustees of the British Museum, London, United Kingdom.", "REICHENBACH, H. G. L. 1846. Die Cetaceen oder Waltiere, nach der neuesten Entdeckungen monographisch zusammengestellt und durch 78 Abbildungen auf XXV: I - XXIV und IIb Kupfertafeln erlautert. Die vollstandige Naturgeschichte des In- und Auslandes, der Saugethiere erster Band. Expedition der Vollstandigsten Naturgeschichte, Dresden, Germany.", "ESCHRICHT, D. F. 1846. Undersogelserne over Hvaldyrene 5. Finhvalernes Osteologie og Artsadskillelse. Kongelige Danske Videnskabernes Selskab Naturvidenskabelig og Mathematisk Afdeling 12: 227 - 396.", "VAN BENEDEN, P. J. 1860. Recherches sur la Fauna littorale de Belgique - Cetaces. Memoires de l'Academie Royale des Sciences et des Sciences, des Lettres et des Beaux-Arts de Belgique 32: 3 - 38.", "CIPRIANO, F. 1997. Antitropical distributions and speciation in dolphins of the genus Lagenorhynchus: a preliminary analysis. Pp. 305 - 316 in Molecular genetics of marine mammals, special publication no. 3 (A. E. Dizon, S. J. Chivers, and W. F. Perrin, eds.). Society for Marine Mammalogy, Lawrence, Kansas.", "LEDUC, R. G., W. F. PERRIN, AND A. E. DIZON. 1999. Phylogenetic relationships among the delphinid cetaceans based on full Cytochrome B sequences. Marine Mammal Science 15: 619 - 648.", "MCGOWEN, M. R., M. SPAULDING, AND J. GATESY. 2009. Divergence date estimation and a comprehensive molecular tree of extant cetaceans. Molecular Phylogenetics and Evolution 53: 891 - 906.", "MCGOWEN, M. R. 2011. Toward the resolution of an explosive radiation - a multilocus phylogeny of oceanic dolphins (Delphinidae). Molecular Phylogenetics and Evolution 60: 345 - 357.", "BANGUERA- HINESTROZA, E., A. HAYANO, E. CRESPO, AND A. R. HOELZEL. 2014. Delphinid systematics and biogeography with a focus on the current genus Lagenorhynchus: multiple pathways for antitropical and trans-oceanic radiation. Molecular Phylogenetics and Evolution 80: 217 - 230.", "WAGNER, A. J. 1846. Die Saugethiere in Abbildungen nach der Natur mit Beschreibungen von d. Johann Christian Daniel von Schreber. Siebenter Theil: Die Ruderfusser und Fischzitzthiere. Expedition des Schreber'schen Saugtier und des Esper'schen Schmetterlingswerkes, Erlangen, Germany.", "WAGNER, A. J. 1847. Die Saugethiere in Abbildungen nach der Natur mit Beschreibungen. Tafelband 2, Theil 4 - 7 und Supplement 3 u. 4: Taf. CLXVI-CCCLXXXIV. Expedition des Schreber'schen Saugtier und des Esper'schen Schmetterlingswerkes, Erlangen, Germany.", "CLAUDIUS, M. 1853. Dissertatio de Lagenorhynchis. C. F. Mohr, Kiliae (Kiel), Germany.", "KINZE, C. C. 2009. White-beaked dolphin Lagenorhynchus albirostris. Pp. 1254 - 1258 in Encyclopedia of marine mammals (W. F. Perrin, B. Wursig, and J. G. M. Thewissen, eds.). 2 nd ed. Academic Press, San Diego, California.", "SUNDEVALL, C. J. 1861. Om nagra Hvalarter. Ofversigt af Kongliga Vetenskaps-Akademiens Forhandlingar 18: 385 - 394.", "BERTULLI, C. G., A. GALATIUS, C. C. KINZE, M. H. RASMUSSEN, W. KEENER, AND M. A. WEBBER. 2016. Color patterns in white-beaked dolphins (Lagenorhynchus albirostris) from Iceland. Marine Mammal Science. doi: 10.1111 / mms 12312.", "HARMER, S. F., 1927. Report on Cetacea stranded on the British coasts from 1913 to 1926. 10 th ed. British Museum of Natural History, London, United Kingdom.", "MERCER, M. C. 1973. Observations on distribution and intraspecific variation in pigmentation patterns of odontocete Cetacea in the western North Atlantic. Journal of the Fisheries Research Board of Canada 30: 1111 - 1130.", "CAMPHUYSEN, C. J. 1991. Het herkennen van de witflankdolfijn Lagenorhynchus acutus en de witsnuitdolfijn Lagenorhynchus albirostris op zee. Huid en Haar 10: 20 - 30.", "REE, V. 1994. Feltbestemmelse af kvitnos og kvitskjeving. En opsummering av artenes utseende i eldre og nyere litteratur og en presentasjon av materiale fra norske farvann de senere ar. Fauna (Oslo) 47: 132 - 165.", "FRASER, F. C. 1974. Report on Cetacea stranded on the British coasts from 1948 to 1966. 14 th ed. British Museum (Natural History), London, United Kingdom.", "GALATIUS, A., O. E. JANSEN, AND C. C. KINZE. 2013 a. Parameters of growth and reproduction of white-beaked dolphins (Lagenorhynchus albirostris) from the North Sea. Marine Mammal Science 29: 348 - 355.", "DONG, J. H., J. LIEN, AND K. CURREN. 1996. A contribution to the biology of the white-beaked dolphin, Lagenorhynchus albirostris, in waters off Newfoundland. Canadian Field Naturalist 110: 278 - 287.", "VAN UTRECHT, W. L. 1981. Comparison of accumulation patterns in layered dentinal tissue of some Odontoceti and corresponding patterns in baleen plates and earplugs of Balaenopteridae. Beaufortia 31: 111 - 122.", "REEVES, R. R., C. SMEENK, C. C. KINZE, R. L. BROWNELL, AND J. LIEN. 1999. White-beaked dolphin Lagenorhynchus albirostris Gray, 1846. Pp. 1 - 29 in Handbook of marine mammals, volume 6: the second book of dolphins and the porpoises (S. H. Ridgway and S. R. Harrison, eds.). Academic Press, San Diego, California.", "WARING, G. T., E. JOSEPHSON, C. P. FAIRFIELD- WASH, AND K. MAZE- FOLEY. 2008. US Atlantic and Gulf of Mexico marine mammal stock assessments. TM F / NE- 210. National Oceanic and Atmospheric Administration, Woods Hole, Massachussetts.", "REINHART, N. R., S. M. E. FORTUNE, P. R. RICHARD, AND C. J. D. MATTHEWS. 2014. Rare sightings of white-beaked dolphins (Lagenorhynchus albirostris) off south-eastern Baffin Island, Canada. Marine Biodiversity Records 7: 1 - 5.", "PIKE, D. G., C. G. M. PAXTON, T. GUNNLAUGSSON, AND G. VIKINGSSON. 2009. Trends in distribution and abundance of cetaceans from aerial surveys in Icelandic coastal waters, 1986 - 2001. NAMMCO Scientific Publications 7: 117 - 142.", "NORTHRIDGE, S. P., M. L. TASKER, A. WEBB, AND J. M. WILLIAMS. 1995. Distribution and relative abundance of harbour porpoises (Phocoena phocoena L.), white-beaked dolphins (Lagenorhynchus albirostris Gray), and minke whales (Balaenoptera acutorostrata Lacepede) around the British Isles. ICES Journal of Marine Science 52: 55 - 66.", "NORTHRIDGE, S. P., M. L. T ASKER, A. W EBB, K. C AMPHUYSEN, AND M. L EOPOLD. 1997. White-beaked dolphin Lagenorhynchus albirostris and Atlantic white-sided dolphin L. acutus distributions in Northwest European and US North Atlantic waters. Reports of the International Whaling Commission 47: 797 - 805.", "HAMMOND, P. S., ET AL. 2002. Abundance of harbour porpoise and other cetaceans in the North Sea and adjacent waters. Journal of Applied Ecology 39: 361 - 376.", "REID, J. B., P. G. H. EVANS, AND S. P. NORTHRIDGE. 2003. Atlas of cetacean distribution in North-West European waters. Joint Nature Conservation Committee, Peterborough, United Kingdom.", "HAMMOND, P. S., ET AL. 2013. Cetacean abundance and distribution in European shelf waters to inform conservation and management. Biological Conservation 164: 107 - 122.", "OIEN, N. 1996. Lagenorhynchus species in Norwegian waters as revealed from incidental observations and recent sighting surveys. Document SC / 48 / SM 15. International Whaling Commission, Scientific Committee, Cambridge, United Kingdom.", "DEGERBOL, M. 1936. Animal remains from the West Settlement in Greenland with special reference to livestock. Meddelelser om Gronland 88: 3 - 54.", "LUTKEN, C. F. 1888. Critical studies upon some Odontoceti of the genera Tursiops, Orca, and Lagenorhynchus. Annals and Magazine of Natural History, 6 th Series 2: 179 - 186.", "TRUE, F. W. 1889. Contributions to the natural history of the cetaceans. A review of the family Delphinidae. Bulletin of the United States National Museum 36: 1 - 191.", "TOMILIN, A. G. 1967. Mammals of USSR and adjoining countries, vol. IX: Cetaceans. Izdatelstvo AN SSSR, Moscow, USSR.", "BUCHHOLTZ, E. A. 2001. Vertebral osteology and swimming style in living and fossil whales (Order: Cetacea). Journal of Zoology 253: 175 - 190.", "GALATIUS, A. 2006. Bilateral directional asymmetry of the appendicular skeleton of the white-beaked dolphin (Lagenorhynchus albirostris). Aquatic Mammals 32: 232 - 235.", "TURNER, W. 1889. Notes on the white-beaked dolphin (Delphinus albirostris). Proceedings of the Physiological Society of Edinburgh 10: 5 - 13.", "JAPHA, A. 1912. Die Haare der Waltiere. Zoologische Jahrbucher (Abteilung Anatomie und Ontogenie der Tiere) 32: 1 - 42.", "WEBER, M. 1887. Ueber Lagenorhynchus albirostris, Gray. Tijdschrift der Nederlandsche Dierkundige Vereeniging 1: 114 - 127.", "CLELAND, J. 1884. Notes on the viscera of the porpoise (Phocaena communis) and the white-beaked dolphin (Lagenorhynchus albirostris). Journal of Anatomy and Physiology 18: 327 - 336.", "VAN NIE, C. J. 1985. The conducting system of the heart of the white-snouted dolphin Lagenorhynchus albirostris (Gray, 1846). Lutra 28: 106 - 112.", "VAN NIE, C. J. 1986. The Purkinje fibres in the heart of the common seal Phocoa vitulina (Linnaeus, 1758), the Baikal seal Pusa siberica (Gmelin, 1788), the fur seal Arctocephalus australis (Zimmermann, 1782), the harbour porpoise Phocoena phocoena (Linnaeus, 1758) and the white-beaked dolphin Lagenorhynchus albirostris (Gray, 1846). Aquatic Mammals 12: 61 - 64.", "MEEK, A. 1918. The reproductive organs of Cetacea. Journal of Anatomy 52: 186 - 210.", "TEN DOESSCHATE, G. 1918. Die Retina von Walembryonen. Anatomischer Anzeiger 51: 200 - 205.", "GALATIUS, A. 2010. Paedomorphosis in two small species of toothed whales (Odontoceti): how and why? Biological Journal of the Linnean Society 99: 278 - 295.", "CANNING, S. J., ET AL. 2008. Seasonal distribution of white-beaked dolphins (Lagenorhynchus albirostris) in UK waters with new information on diet and habitat use. Journal of the Marine Biological Association of the United Kingdom 88: 1159 - 1166.", "FERNANDEZ, R., ET AL. 2016. A genomewide catalogue of single nucleotide polymorphisms in white-beaked and Atlantic white-sided dolphins. Molecular Ecology Resources 16: 266 - 276.", "CETACEAN AND TURTLE ASSESSMENT PROGRAM. 1982. A characterization of marine mammals and turtles in the mid- and north Atlantic areas of the U. S. outer continental shelf. Cetacean and Turtle Assessment Program, University of Rhode Island. Final Report AA 551 - CT 8 - 48 to the Bureau of Land Management, Washington, D. C.", "MACLEOD, C. D. 2014. One size does not necessarily fit all for cetacean abundance estimate survey design - reply to Hammond. Biological Conservation 170: 336 - 337.", "HAMMOND, P. S., ET AL. 2014. Large scale surveys for cetaceans: line transect assumptions, reliability of abundance estimates and improving survey efficiency - a response to MacLeod. Biological Conservation 170: 338 - 339.", "JANSEN, O. E., M. F. LEOPOLD, E. H. W. G. MEESTERS, AND C. SMEENK. 2010. Are white-beaked dolphins Lagenorhynchus albirostris food specialists? Their diet in the southern North Sea. Journal of the Marine Biological Association of the United Kingdom 90: 1501 - 1508.", "KINZE, C. C., ET AL. 1997. The white-beaked dolphin (Lagenorhynchus albirostris) and the white-sided dolphin (Lagenorhynchus acutus) in the North and Baltic Seas: review of available information. Reports of the International Whaling Commission 47: 675 - 681.", "WEIR, C. R., C. POLLOCK, C. CRONIN, AND S. TAYLOR. 2001. Cetaceans of the Atlantic Frontier, north and west of Scotland. Continental Shelf Research 21: 1047 - 1071.", "MACLEOD, C. D., C. R. WEIR, C. PIERPOINT, AND E. J. HARLAND. 2007. The habitat preferences of marine mammals west of Scotland (UK). Journal of the Marine Biological Association of the United Kingdom 87: 157 - 164.", "MACLEOD, C. D., ET AL. 2005. Climate change and the cetacean community of north-west Scotland. Biological Conservation 124: 477 - 483.", "WEIR, C. R., K. A. STOCKIN, AND G. J. PIERCE. 2007. Spatial and temporal trends in the distribution of harbour porpoises, white-beaked dolphins and minke whales off Aberdeenshire (UK), north-western North Sea. Journal of the Marine Biological Association of the United Kingdom 87: 327 - 338.", "FRASER, F. C., 1946. Report on Cetacea stranded on the British coasts from 1933 to 1937. 12 th ed. British Museum (Natural History), London, United Kingdom.", "EVANS, P. G. H. 1980. Cetaceans in British waters. Mammal Review 10: 1 - 52.", "EVANS, P. G. H. 1987. The natural history of whales and dolphins. Academic Press, London, United Kingdom.", "LICK, R. 1994. Nahrungsanalysen von Kleinwalen deutscher Kustengewasser. University of Kiel, Kiel, Germany.", "DAS, K., ET AL. 2003 a. Marine mammals from Northeast Atlantic: relationship between their trophic status as determined by delta C- 13 and delta N- 15 measurements and their trace metal concentrations. Marine Environmental Research 56: 349 - 365.", "DAS, K., G. LEPOINT, Y. LEROY, AND J. M. BOUQUEGNEAU. 2003 b. Marine mammals from the southern North Sea: feeding ecology data from delta C- 13 and delta N- 15 measurements. Marine Ecology Progress Series 263: 287 - 298.", "OSTERHAUS, A. D. M. E., ET AL. 1995. Morbillivirus infections of aquatic mammals - newly identified members of the genus. Veterinary Microbiology 44: 219 - 227.", "WOHLSEIN, P., C. PUFF, M. KREUTZER, U. SIEBERT, AND W. BAUMGARTNER. 2007. Distemper in a dolphin. Emerging Infectious Diseases 13: 1959 - 1961.", "VAN ELK, C. E., ET AL. 2014. Is dolphin morbillivirus virulent for whitebeaked dolphins (Lagenorhynchus albirostris). Veterinary Pathology 51: 1174 - 1182.", "OSTERHAUS, A. D. M. E., ET AL. 1993. Isolation of a virus with rhabdovirus morphology from a white-beaked dolphin (Lagenorhynchus albirostris). Archives of Virology 133: 189 - 193.", "KOMPANJE, E. J. O. 1995. Spondylosis deformans in white-beaked dolphins. Zoologische Mededelingen Leiden 69: 231 - 250.", "GALATIUS, A., C. SONNE, C. C. KINZE, R. DIETZ, AND J. E. B. JENSEN. 2009. Occurrence of vertebral osteophytosis in a museum sample of whitebeaked dolphins (Lagenorhynchus albirostris) from Danish waters. Journal of Wildlife Diseases 45: 19 - 28.", "BERTULLI, C. G., ET AL. 2015. Vertebral column deformities in whitebeaked dolphins from the eastern North Atlantic. Diseases of Aquatic Organisms 116: 59 - 67.", "KRABBE, H. 1878. Saelernes og Hvalernes Spolorme. Oversigt over det Kongelige Videnskabernes Selskabs Forhandlinger 1878: 43 - 51.", "RAGA, J. A. 1994. Parasitismus bei Cetacea. Pp. 132 - 179 in Handbuch der Saugetiere Europas Bd. 6 / 1 A (D. Robineau, R. Duguy, and M. Klima, eds.). Aula-Verlag, Wiesbaden, Germany.", "BERTULLI, C., A. CECHETTI, M. - F. VAN BRESSEM, AND K. VAN WAEREBEEK. 2012. Skin disorders in common minke whales and white-beaked dolphins off Iceland, a photographic assessment. Journal of Marine Animals and Their Ecology 5: 29 - 40.", "MUIR, D. C. G., R. WAGEMANN, N. P. GRIFT, R. J. NORSTROM, M. SIMON, AND J. LIEN. 1988. Organochlorine chemical and heavy metal contaminants in white-beaked dolphins (Lagenorhynchus albirostris) and pilot whales (Globicephala malaena) from the coast of Newfoundland, Canada. Archives of Environmental Contamination and Toxicology 17: 613 - 629.", "DIETZ, R., ET AL. 1998. Heavy metals. Pp. 373 - 524 in AMAP Assessment Report: Arctic Pollution Issues. Arctic Monitoring and Assessment Programme, Oslo, Norway.", "LAW, R. J., ET AL. 1991. Concentrations of trace metals in the livers of marine mammals (seals, porpoises and dolphins) from waters around the British Isles. Marine Pollution Bulletin 22: 183 - 191.", "SIEBERT, U., ET AL. 1999. Potential relation between mercury concentrations and necropsy findings in cetaceans from German waters of the North and Baltic Seas. Marine Pollution Bulletin 38: 285 - 295.", "DIETZ, R., ET AL. 2013. What are the toxicological effects of mercury in Arctic biota? Science of the Total Environment 443: 775 - 790.", "GASKIN, D. E. 1982. The ecology of whales and dolphins. Heinemann, London, United Kingdom.", "HARMS, U., H. E. DRESCHER, AND E. HUSCHENBETH. 1978. Further data on heavy metals and organochlorines in marine mammals from German coastal waters. Meeresforschung 26: 153 - 161.", "VIALE, D. 1978. Evidence of metal pollution in Cetacea of the western Mediterranean. Annales de l'Institut Oceanographique (Paris) 54: 5 - 16.", "HELLE, E., M. OLSSON, AND S. JENSEN. 1976. DDT and PCB levels and reproduction in ringed seal from the Bothnian Bay. Ambio 5: 188 - 189.", "VAN DE VIJVER, K. I., ET AL. 2003. Perfluorinated chemicals infiltrate ocean waters: link between exposure levels and stable isotope ratios in marine mammals. Environmental Science & Technology 37: 5545 - 5550.", "DIETZ, R., ET AL. 2015. Physiologically-based pharmacokinetic modelling of immune, reproductive and carcinogenic effects from contaminant exposure in polar bears (Ursus maritimus) across the Arctic. Environmental Research 140: 45 - 55.", "GALATIUS, A., ET AL. 2013 b. PFAS profiles in three North Sea top predators: metabolic differences among species? Environmental Science and Pollution Research 20: 8013 - 8020.", "HAUG, T., B. GULLINKSEN, AND I. CHRISTENSEN. 1981. Observations of the common dolphin, (Delphinus delphis), in North Norway. Fauna (Oslo) 34: 97 - 100.", "JONES, P. H. 1984. Cetaceans seen in the Irish Sea and approaches, late summer 1983. Nature in Wales 3: 62 - 64.", "JEEWOONARAIN, T., E. C. M. PARSONS, AND P. G. H. EVANS. 1999. Operation sightings: sightings of cetaceans in the Southern Hebrides, Scotland. European Research on Cetaceans 13: 237 - 241.", "HAASE, B. J. M. 1987. A mixed herd of white-beaked dolphins Lagenorhynchus albirostris and white-sided dolphins Lagenorhynchus acutus in the southern North Sea. Lutra 30: 105 - 106.", "DE BOER, R. 1989. Waarneming van een gemengde groep witflankdolfijnen Lagenorhynchus acutus en witsnuitdolfijnen L. albirostris in de centrale Nordzee. Lutra 32: 181 - 189.", "MACLEOD, C. D., C. R. WEIR, M. B. SANTOS, AND T. E. DUNN. 2008. Temperature-based summer habitat partitioning between whitebeaked and common dolphins around the United Kingdom and Republic of Ireland. Journal of the Marine Biological Association of the United Kingdom 88: 1193 - 1198.", "WEIR, C. R., C. D. MACLEOD, AND S. V. CALDERAN. 2009. Fine-scale habitat selection by white-beaked and common dolphins in the Minch (Scotland, UK): evidence for interspecific competition or coexistence? Journal of the Marine Biological Association of the United Kingdom 89: 951 - 960.", "BRITISH BROADCASTING CORPORATION. 2012. Killer whales hunting dolphins in Scotland photographed. http: // www. bbc. com / news / uk-scotlandhighlands-islands- 18175090. Accessed 20 January 2015.", "JEFFERSON, T. A., P. J. STACEY, AND R. W. BAIRD. 1991. A review of killer whale interactions with other marine mammals: predation to co-existence. Mammal Review 21: 151 - 180.", "MEHLUM, F., G. L. HUNT, M. B. DECKER, AND N. NORDLUND. 1998. Hydrographic features, cetaceans and the foraging of thick-billed murres and other marine birds in the northwestern Barents Sea. Arctic 51: 243 - 252.", "EVANS, P. G. H. 1982. Associati